2023
DOI: 10.1097/gox.0000000000004833
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Antibiotics for Deep Inferior Epigastric Perforator Flap Breast Reconstruction: A Comparison between Three Different Duration Approaches

Abstract: Background: There is no consensus on the duration of prophylactic antibiotic use for autologous breast reconstruction after mastectomy. We attempted to standardize the use of prophylactic antibiotics after mastectomy using a deep inferior epigastric perforator flap for the breast reconstruction procedure. Methods: This retrospective case series included 108 patients who underwent immediate breast reconstruction with a deep inferior epigastric perforator flap at the Ditmanson Medical Foundation Chia-Yi Christia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The location of reported SSIs within the studies analysed is generally insufficient. Liu et al reported a total of 44 (17.1%) SSIs which had an even distribution between the donor site and recipient site, Changchien et al reported a single SSI (1.2%) which affected the recipient site, and Drury et al did not mention the site in which SSIs occurred [11][12][13]. Liu et al showed insignificant differences in terms of SSI rates for the prolonged antibiotic duration with subgroup analyses including obesity, smoking, and age [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The location of reported SSIs within the studies analysed is generally insufficient. Liu et al reported a total of 44 (17.1%) SSIs which had an even distribution between the donor site and recipient site, Changchien et al reported a single SSI (1.2%) which affected the recipient site, and Drury et al did not mention the site in which SSIs occurred [11][12][13]. Liu et al showed insignificant differences in terms of SSI rates for the prolonged antibiotic duration with subgroup analyses including obesity, smoking, and age [12].…”
Section: Discussionmentioning
confidence: 99%
“…Changchien et al [11] Changchien et al conducted a cohort study comprising 108 patients undergoing breast reconstruction with a DIEP flap. Patients were divided into three groups based on the duration of antibiotic prophylaxis (one, three, and more than seven days), and the occurrence of SSIs was identified in each group and compared.…”
Section: Description Of Studiesmentioning
confidence: 99%